Looking for free-riding: Energy efficiency incentives and Italian homeowners - Anna Alberini; Andrea Bigano; Marco Boeri (Fondazione Eni Enrico Mattei (FEEM), 2013)
We examine the effect of energy efficiency incentives on household energy-efficiency home improvements. Starting in February 2007, Italian homeowners have been able to avail themselves of tax credits on the purchase and installation costs of certain types of energy efficiency renovations. We examine two such renovations-door/windows replacements and heating system replacements-using multi-year cross-section data from the Italian Consumer Expenditure Survey and focusing on a narrow period around the introduction of the tax credits. Our regressions control for dwelling and household characteristics and economy-wide factors likely to influence the replacement rates. The effects of the policy are different for the two types of renovations. With window replacements, the policy is generally associated with a 30% or stronger increase in the renovation rates and number of renovations. In the simplest econometric models, the effect is not statistically significant, but the results get stronger when we allow for heterogeneous effects across the country. With heating system replacements, simpler models suggest that the tax credits policy had no effect whatsoever or that free riding was rampant, i.e., people are now accepting subsidies for replacements that they would have done anyway. Further examination suggests a strong degree of heterogeneity in the effects across warmer and colder parts of the country, and effects in the colder areas that are even more pronounced than those for windows replacements. These results should, however, be interpreted with caution due to the low rate of renovations and the imprecisely estimated effects.
Keywords: Q41; D12; H3; 330; Energy Efficiency Policy; Household Behavior; Italy; Energy Consumption Survey